Comparative study between chlorhexidine and sodium hypochlorite as disinfectant solutions in endodontic practice, review - Andrade, Cesar (2017)
The success of endodontic treatments depends both on a good conformation of the root canals and on the correct disinfection of the pulp space, since the organisms that live in the walls of the root canals can survive as monocultures. Mechanics of lipopolysaccharides is the use of irrigators such as sodium hypochlorite which is one of the most widely used irrigators for the disinfection of root canals as it allows us to dissolve organic tissues in addition to their strong antimicrobial activity, chlorhexidine that has biocompatible characteristics in addition to Two characteristics useful at the time of disinfection of the root canal, such as sustainability and its antimicrobial action or ethylenediaminetetraacetic acid (EDTA), which has chelating characteristics that allow the elimination of the smear layer or dentin barrel product of mechanical instrumentation Of the root canals as well as favoring the action of other irrigators to reach the dentinal tubules and their ramifications.